A New Global Database of Lunar Impact Craters >1–2 km: 1. Crater Locations and Sizes, Comparisons With Published Databases, and Global Analysis. Issue 4 (3rd April 2019) - Robbins, Stuart J.
Abstract: This paper presents a new, global database of lunar impact craters, estimated to be a complete census of all craters with diameters larger than 1–2 km. The database contains over 2 million craters, making it larger in number than any previously published lunar effort by more than a factor of 10. Of those craters, 1.3 million have diameters ≥1 km, approximately 83, 000 are ≥5 km, and 6, 972 craters are ≥20 km. How the database was constructed along with the reliability of features is described in detail. Comparisons are made with past published databases, demonstrating good agreement for crater size and location. An ellipticity analysis is conducted, illustrating there is no dominant direction for elliptical crater orientation based on location, diameter range, or ellipticity amount, consistent with randomness for craters ≥10 km. A spatial density analysis is described, comparing the spatial density of small versus large craters, and numerous observations about the nonuniformity of the size distributions of craters across the Moon are made. The spatial density is also used in a discussion about kilometer‐scale secondary impact craters and clearly shows that they dominate the crater population in some areas of the lunar surface. This paper presents just a tiny sample of the scientific investigations that could be done with this new crater database. Plain Language Summary: This work presents a new database of lunar impact craters. Over 2 million craters were identified and measured, and 1.3 million of them are larger than 1 km in diameter. The database is estimated to be a complete census of all craters larger than approximately 1 to 2 km across. Where there are overlaps, this database compares well with past databases with respect to crater diameters and locations, but the database contains more craters smaller than about 20 km across than any other crater database. This increase is attributed primarily to the fully manual effort involved in searching multiple instruments' data sets, using both imagery and topography, and multiple searches of the lunar surface. A spatial density analysis of the craters in different diameter ranges shows many trends that have been seen before, but it also reveals details of nonuniformity, which have not been previously described, including an enhanced small crater population at the Moon's north pole and many effects of secondary craters—craters that form from the ejecta of a larger, primary impact. Additionally, the database contains ellipse properties of the craters, and it shows that large craters' orientations are indistinguishable from randomness. Key Points: Of the identified and measured >2 million lunar craters, 1.3 million are ≥1 km in diameter Found more craters ≲30 km than all other published catalogs, likely due to multiple data sets used and including subdued and secondary craters More elliptical craters are found than past work, orientation of D  ≥ 10 km craters are random, and many spatial density trends are discussed